Experimental determination of fatigue life for international rubber hardness degree 60 engine mount rubber - Hosseini, Maryam (2010)
In the new millennium era, rubber materials are vigorously used in many industries including automotive that cover a wide range of applications such as tires, seals, belts, bushes and engine mounts. Rubber is an ideal material for many applications because it can withstand very large strain with no permanent deformation or fracture. The behavior of material under repeated loads differs from static loads. Elastomers fail at cyclic stress or strain amplitude much lower than static stress or strain. It is based on growth of cracks through the material. The fatigue analysis and its lifetime evaluation are very important in design procedure to assure the safety and reliability of the rubber components. Design of rubber against fatigue failure is one of the important topics to be focussed for checking the failures during its operation life. Many mechanical and environmental factors could prolong the rubber fatigue life. The fatigue failure process of materials is explained by two approaches including crack initiation and crack propagation. The present work deals with investigation of the fatigue behavior using rubber dumbbell test specimens under uniaxial loading. The material used in this study is a vulcanized natural rubber with a typical engine mount formulation and the hardness of International Rubber Hardness Degree 60. Test specimens were designed based on type 2 of MS ISO 37 standard and used for tensile and fatigue tests, both in ambient temperature. Fatigue tests were conducted under the displacement controlled condition with a sine waveform of 0.1 Hz and the ratio of the minimum displacement to the maximum displacement was equal to zero. The experimental results were presented under strain controlled condition. For investigation of the fatigue damage behavior, a theoretical equation was developed based on the continuum damage mechanics theory. The Ogden strain energy potential of first order was used for defining a constitutive relation of the natural rubber. The proposed theoretical formula was based on function of the strain range under cyclic loading to determine the fatigue life of elastomeric material. The ability of predicted fatigue life shows a reasonable agreement of 98% with experimental values. The experimental results and theoretical equation were validated with the previous experimental data which show a good agreement of 97% and 93% respectively.